Desenvolvimento de lipossomas híbridos contendo fragmentos de membranas de células tumorais para imunoestimulação na terapia antitumoral - Gonçalves, Marcilia Viana Pavam (2019)
A lot of progress has been made in the past decades in the development of nanoparticles as carriers of antitumor drugs, and today, with the successes achieved with cancer immunotherapy, many advances have been made with the use of nanoparticles to arouse effective immune response against tumor cells. In this study, hybrid synthetic phospholipids associated to phospholipids and cell membrane proteins from B16F10 cells were developed. Through the microfluidization technique hybrid liposomes of 130 µm average diameter were obtained. Thus, by studying the membrane fluidity and mobility, the interaction between the phospholipids could be confirmed by the Electron Paramagnetic Resonance (EPR) technique. Finally, a model of murine cutaneous melanoma was standardized from the inoculation of cells of tumor line B16F10, the same ones used to obtain hybrid liposomes, in order to pave the way for future studies on the in vivo immune response.